A decentralized strategy of structural reconfiguration in mitigation of vibrations. (2017) - Poplawski, Blazej; Mikułowski, Grzegorz; Mróz, Arkadiusz; Sekuła, Krzysztof; Jankowski, Łukasz
Abstract: This contribution proposes a decentralized closed-loop control algorithm for semi-active mitigation of free vibrations in frame structures. The control uses dedicated dissipative devices, which consist of two controllable structural nodes placed pairwise in both ends of selected structural beams. The nodes are capable of a controlled transition between the standard frame mode of operation (full moment-bearing ability) and the truss mode in which they do not bear any moments and constitute in fact structural hinges. Syncronous switching is equivalent to reconfiguration of the global structure by (dis)allowing the involved beams to transmit moments and to accumulate vibration energy in the form of their bending strain. Upon switching to the truss mode, the accumulated energy is released into high-frequency local vibrations, which undergo quick dissipation by standard mechanisms of material damping. The approach is illustrated in a numerical example and verified in a preliminary experimental test.